Paying off populism: How regional policies affect voting behavior - Robert Gold; Jakob Lehr (Kiel Institute for the World Economy (IfW Kiel), 2024)
This paper shows that regional policies can decrease populist support. We focus on the "development objective" (Objective-1) of the European Regional Development Fund (ERDF), meant to support lagging-behind regions. For causal inference, we exploit three sources of quasi-exogenous variation in a Regression-Discontinuity-Design (RDD), a Difference-in-Differences framework (DiD), and with matching techniques. Using NUTS3-level panel data on the outcomes of elections to the EU parliament, observed over the period 1999-2019, we consistently find that Objective-1 transfers reduces the vote share of right-fringe parties by about 2.5 pp. Left-fringe party support is not affected. Complementary analyses of individual-level survey data from the Eurobarometer show that the European Regional Policy increases trust in democratic institutions and decreases discontent with the EU.
Keywords: D72; H54; R11; R58; 330; Populism; Regional Policies; European Integration; Regression Discontinuity Design